Intelligent Missile Guiding Technology - Kanta Dash, Mukti; Pattanaik, Priyabrata (International Journal of Psychosocial Rehabilitation, 2025)
This paper is concentrated on utilization of GPS and “Relative GPS/ATACMS Scenario”. The rocket can be guided by various ways, for instance by utilizing radio waves, infrared, laser and also by utilizing GPS and INS. Radio waves are utilized when rocket is guided by a human administrator or by utilizing radar architecture. Infrared is utilized to manage the rocket when target produces heat energy. With the assistance of infrared heat energy produced by the objective which is distinguished, at that point rocket is guided by following warmth produce by the objective. Laser direction works by pointing laser on the object, at that point rocket is guided by the laser beam. Finally, the advantages and limitations of the GPS based missiles/rockets were discussed